2022
DOI: 10.1038/s41391-022-00588-5
|View full text |Cite|
|
Sign up to set email alerts
|

Survival of veterans treated with enzalutamide and abiraterone for metastatic castrate resistant prostate cancer based on comorbid diseases

Abstract: BackgroundComorbid diseases in uence patient outcomes, yet little is known about how comorbidities interact with treatments for metastatic castrate-resistant prostate cancer (mCRPC). No head-to-head trials have compared the e cacy of abiraterone and enzalutamide -oral androgen-receptor targeted agents (ARTAs) for mCRPC. In patients with comorbid disease, outcomes with ARTAs may differ due to disparate mechanisms of action, adverse events, and drug interactions. MethodsRetrospective observational study of US ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…It shows that the OS was longer in patients treated with ENZA than ABI (24.2 vs 22.1 months) in pre- and post-chemotherapy treated patients. Importantly, patients with cardiovascular diseases also had better survival ( 9 ). Also, a direct comparison of drugs in 10,308 chemotherapy-naive patients with CRPC based on the 2014-2018 French population study showed that patients treated with ENZA had a better OS than ABI (34.2 vs. 31.7 mo.)…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the OS was longer in patients treated with ENZA than ABI (24.2 vs 22.1 months) in pre- and post-chemotherapy treated patients. Importantly, patients with cardiovascular diseases also had better survival ( 9 ). Also, a direct comparison of drugs in 10,308 chemotherapy-naive patients with CRPC based on the 2014-2018 French population study showed that patients treated with ENZA had a better OS than ABI (34.2 vs. 31.7 mo.)…”
Section: Discussionmentioning
confidence: 99%
“…We used the Medical Dictionary for Regulatory Activities (MedDRA, version 25.0) to treat each AE as a preferred term (PT) and grouped it into the System Organ Class (SOC). 16 We excluded several AEs to avoid false-positives when the total reported number in the PT level was <50. In total, we analyzed 285 AEs (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Schoen et al retrospectively evaluated survival of patients with mCRPC treated with enzalutamide (ENZA) or abiraterone (ABI) based on comorbidities [10]. Their study evaluated 5822 patients with 43% receiving ENZA and 57% receiving ABI.…”
Section: Survival Of Veterans Treated With Enzalutamide and Abiratero...mentioning
confidence: 99%